Pharmacological Actions of Eladwaya (Elettaria Cardamomum Maton and Amomum Subulatum Roxb) - A Review - Rabb, Umakant N (International Research Journal of Ayurveda & Yoga, 2022)
The two varieties of cardamom i.e Ela Dwaya viz; (Elettaria cardamomum Maton and Amomum subulatum Roxb). The Sookshma Ela(Elettaria cardamom) is considered as the queen of spices. The Ela(Elettaria cardamomum Maton) acts as stimulant. Both cardamom are herbaceous perennial plants belong to Zingiberaceae family. Extensively grow in South India. It is an excellent anti oxidant. It helps to relieve Daha(Burning sensation) and gastritis. It helps to relieve xerostomia(Dry mouth) and bad breath due to itʾs antibacterial actions. The Elettaria cardamomum Maton and Amomum subulatum Roxb help to alleviate Shotha(Inflammation), Shirshula(Headache), Karnashula(Earache), Danta Shula(Toothache), Yakrit Vikara(Disorders of liver), chest, Kantha Vikara(Throat diseases) due to itʾs anti inflammatory and analgesic activities. The second variety is Brihat Ela(Amomum subulatum) is black cardamom also called hill cardamom. It is perennial herbaceous plant belongs to the same family Zingiberaceae. The seed pods have a strong, camphor like flavour and are also used as spice similar to the green cardamom pods. The black cardamom is used for Udara Vikara(Stomach disorder) due to its gastroprotective action, and Jwara(Malarial fever) due to anti inflammatory and analgesic actions. The drug showed the importance of chemical constituents including carbohydrates, proteins, minerals, lipids, essential oils, flavonoids, terpenoids, caratenoids. The drug powder also helps in chronic cigarette de addiction. The present work dealt with the data were obtained by several electronic scientific databases, articles, and the additional information was collected from the various Ayurvedic classical texts.